The Chromatin Environment Around Interneuron Genes in Oligodendrocyte Precursor Cells and Their Potential for Interneuron Reprograming - Boshans, Linda L.; Factor, Daniel C.; Singh, Vijender; Liu, Jia; Zhao, Chuntao; Mandoiu, Ion; Lu, Q. Richard; Casaccia, Patrizia; Tesar, Paul J.; Nishiyama, Akiko (Frontiers in Neuroscience, 2019)
Oligodendrocyte precursor cells (OPCs), also known as NG2 glia, arise from neural progenitor cells in the embryonic ganglionic eminences that also generate inhibitory neurons. They are ubiquitously distributed in the central nervous system, remain proliferative through life, and generate oligodendrocytes in both gray and white matter. OPCs exhibit some lineage plasticity, and attempts have been made to reprogram them into neurons, with varying degrees of success. However, little is known about how epigenetic mechanisms affect the ability of OPCs to undergo fate switch and whether OPCs have a unique chromatin environment around neuronal genes that might contribute to their lineage plasticity. Our bioinformatic analysis of histone posttranslational modifications at interneuron genes in OPCs revealed that OPCs had significantly fewer bivalent and repressive histone marks at interneuron genes compared to astrocytes or fibroblasts. Conversely, OPCs had a greater degree of deposition active histone modifications at bivalently marked interneuron genes than other cell types, and this was correlated with higher expression levels of these genes in OPCs. Furthermore, a significantly higher proportion of interneuron genes in OPCs than in other cell types lacked the histone posttranslational modifications examined. These genes had a moderately high level of expression, suggesting that the “no mark” interneuron genes could be in a transcriptionally “poised” or “transitional” state. Thus, our findings suggest that OPCs have a unique histone code at their interneuron genes that may obviate the need for erasure of repressive marks during their fate switch to inhibitory neurons.